The Role of Digital Technologies in Fostering Research Competence among Future Specialists - Chashechnikova, Olga; Odintsova, Oksana; Chukhrai, Zoriana; Kulchytska, Nataliia; Bielikova, Olena; Ishutina, Olena; Imber, Viktoriia; Radul, Valerii; Puchkov, Ihor; Lytvynenko, Iryna (International Journal of Basic and Applied Sciences, 2025)
The significance of using digital technologies in developing the research competence of future specialists is proven. The basic principles of ‎developing educational software are described. Competencies are identified, the mastery of which will confirm the development of research ‎competence of future specialists by forming research skills through the use of digital technologies. A study was conducted based on empirical distributions. Qualitative and quantitative indicators of the samples were analysed. The consistency of the obtained results of each com‎ponent was checked using the Pearson χ2 criterion (non-parametric). Respondents in the control and experimental groups are equivalent, ‎making it impossible to influence the accuracy and reliability of the results during the experiment’s formative stage. The analysis of the results of the experiment we conducted confirms the usefulness of the author’s pedagogical conditions and methods for developing research ‎competence among future specialists through the use of digital technologies. A comparison of quantitative indicators of CG and EG at the ‎beginning and after the experimental study revealed significant positive changes in the training of specialists to advance research competence ‎through the use of digital technologies‎.